IMPLEMENTATION OF THE MERDEKA CURRICULUM IN INDONESIA: CHALLENGES AND OPPORTUNITIES - Fajri, Taufik Akbar Al; Andarwulan, Trisna (Erudio Journal of Educational Innovation, 2023)
The curriculum is constantly changing to keep up with existing trends. Since Indonesia officially became an independent country in 1945, there have been 12 changes to the national education curriculum. The most recent change occurred with the Curriculum 2013, commonly known as K13, which now incorporates the Merdeka Learning Curriculum. The Merdeka Learning Curriculum is introduced as a learning method that follows a talent and interest-based approach. Students can choose the subjects they want to study based on their passions, aiming to produce a younger generation in Indonesia ready to face the future and global challenges. This research falls under the category of a case study with a qualitative approach. Opportunities in the implementation process of the independent learning policy in the classroom allow teachers the freedom to fully control the class. With this independent learning curriculum, teachers have more flexibility to provide opportunities to students based on their capacities, and students are not required to be uniform in their learning experiences. One of the challenges in implementing the independent curriculum is the attitudes/tendencies of the implementers. The understanding of implementers regarding general goals, basic standards, and policy objectives is crucial. In conclusion, the independent learning curriculum provides freedom to both students and teachers in their learning patterns. In the independent learning curriculum, students are required to be more active and interactive in the learning process. An important factor for each individual is to have a complete understanding of the independent learning curriculum, making it easier to achieve the expected goals.